Defining and developing data literacy [version 1; peer review: 2 approved, 1 approved with reservations] - Deanna Kuhn (Routledge Open Research)
Courses in data literacy, along with electronic tools to support them, have quickly sprung up for students from elementary through college levels, prompted in part by an increasingly apparent need for people of all ages to interpret data they encounter in popular media, as a requisite for responsible citizenship. What and how do students learn with the aid of such tools? As valuable as these may be in presenting data in varying transformable formats, they can be at most a beginning tool in a developmental progression toward data literacy that needs to be identified. Might at least the early phases of this development be accomplished as well or better without such tools? Data literacy does not emerge in one piece. What challenges do students encounter as they advance in a learning progression? Relevant to how they may do so is research on the development of higher-order inductive reasoning, in particular the coordination of theory and evidence in causal and explanatory reasoning. Possibly, very simple data displays provide young students all the complexity they need to address the initial conceptual challenges awaiting them.